Peran Perpustakaan Umum dalam Mengakomodasi Kebutuhan Anak Neurodivergen di Perpustakaan Jakarta-Cikini - Idamatussilmi, Fina; Fauziah, Kiki (UI Scholars Hub, 2025)
Libraries have the opportunity to create a welcoming environment for neurodivergent individuals and promote the importance of inclusive access for everyone in the community. This study aims to identify the facilities and programs provided by the Jakarta-Cikini Library that can play a role in accommodating the needs of neurodivergent children. This research was conducted using a qualitative approach and a case study method. Informants were selected through purposive sampling. Data collection was conducted over a four-month period, from March 2023 to June 2023, using observation, interviews, and documentation techniques. Informants in this study were the children's services librarian responsible for inclusion services and the neurodivergent child's companion. The results of this study indicate that the facilities and programs at the Jakarta-Cikini Library have played a role in accommodating the needs of neurodivergent children. The provision of various games in the Storytelling Room and the implementation of several programs in the Play Room related to sensory and motor activities support the needs of neurodivergent children. Training is also conducted for library staff to serve users with mental and intellectual disabilities. The obstacles experienced by the Jakarta-Cikini Library include budgeting for facilities needed by neurodivergent users and difficulty scheduling training time for library staff. With this, it is hoped that the Jakarta-Cikini Library will understand the importance of accommodating the needs of neurodivergent children so that it can continue to improve its services.